Socio-demographic insights into South African student drinking behaviour - Lategan, B.W.; du Preez, R.; Pentz, C.D. (South African Journal of Higher Education, 2017)
Hazardous and harmful drinking is on the rise among adolescents and young adults and has been classified as a major health problem. University students is a subgroup of young adults that are characterised by more frequent, and even more dangerous drinking behaviours than their non-student peers and new intervention approaches are needed to foster behavioural change. The purpose of this study is to investigate the drinking behaviour and socio-demographic profile of a cohort of South African university students and propose future research avenues to address student drinking behaviour. Ex post facto survey data was collected by means of a questionnaire including the Alcohol Use Disorder Identification Test (AUDIT) and a demographic section. Data was gathered from university students (n=474) from a single campus within South Africa. Data analysis included descriptive statistics, reliability analysis, independent sample t-tests and one-way ANOVAs. Results indicate significant differences in drinking behaviour for gender groups; age; level of disposable income; type of beverage consumed, binge drinking, level and frequency of consumption. The findings have implications for higher education management, public health authorities, and academia and provide valuable insight on the socio-demographic profile and drinking behaviour of a cohort of university students. The findings serve as a foundation for future research into the development of a persuasive communications strategy (educational and prevention campaigns) that could foster much needed behavioural change.